Engineering broad-spectrum resistance to cotton leaf curl disease by CRISPR-Cas9 based multiplex editing in plants. Issue 2 (31st December 2021) - Mubarik, Muhammad Salman; Wang, Xiukang; Khan, Sultan Habibullah; Ahmad, Aftab; Khan, Zulqurnain; Amjid, Muhammad Waqas; Razzaq, Muhammad Khuram; Ali, Zulfiqar; Azhar, Muhammad Tehseen
ABSTRACT: Advances in genome editing technologies have tremendous potential to address the limitations of classical resistance breeding. CRISPR-Cas9 based gene editing has been applied successfully in plants to tolerate virus infections. In this study, we successfully tested CRISPR-Cas9 system to counteract cotton leaf curl disease (CLCuD) caused by whitefly transmitted cotton leaf curl viruses (CLCuVs). We also analyzed the ability of CLCuV to escape the Cas9 endonuclease activity. Targeting overlapping genes of most prevalent CLCuVs with three gRNAs resulted in virus interference, as validated by low virus titer. Furthermore, multiplex CRISPR-Cas9 construct simultaneously targeting six genes of CLCuV, was found more effective to interfere with virus proliferation compared to targeting single region individually. Additionally, transgenic N. benthamiana plants expressing multiple gRNAs simultaneously showed enhanced tolerance against CLCuV infection when compared to wild-type plants. T7 Endonuclease-I (T7EI) assay, showing indels in the CLCuV genome, confirmed the occurrence of double strand breaks (DSBs) in DNA at target sequence induced by Cas9 endonuclease. We observed that targeting CLCuV genome at multiple sites simultaneously resulted in better interference, also with inefficient recovery of altered virus molecules. Next, we tested multiplex construct in cotton to interfere CLCuV infection. We found significant decrease in virus accumulation in cotton leaves co-infiltrated with multiplex cassette and virus compared to cotton leaves infiltrated with virus only. The results demonstrate future use of CRISPR-Cas9 system for engineering virus resistance in crops. Moreover, our results also advocate that resistance to mixed virus infections can be engineered using multiplex genome editing.